2018
DOI: 10.5812/traumamon.13079
|View full text |Cite
|
Sign up to set email alerts
|

Blunt Thoracic Injury Mortality and Clinical Presentation

Abstract: Background: Blunt thoracic trauma is the third most common injury in poly-trauma patients following head and extremities injuries; this study aimed at investigating the prevalence of blunt chest trauma and its injury pattern, mechanism of injury, length of hospital stay, treatment period, and risk factors. Methods: In this cross-sectional study, 7,410 patients, who referred to Shahid Rajaee hospital, during years 2010 to 2014 were selected through census sampling. The participants' demographic data, mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
3
5
0
Order By: Relevance
“…Although we did not find any correlation of rib fractures with mortality (p=0.06), Yadollahi et al in their work reported more than thrice the risk of mortality in blunt trauma patients with rib fractures. Their mortality risk was not associated with hemothorax (p≥0.05) [ 4 ] as in our study. Literature has reported varying frequencies of hemothorax, hemopneumothorax, pneumothorax, rib fractures, and lung contusions in patients with thoracic trauma [ 6 , 11 , 17 , 18 ].…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…Although we did not find any correlation of rib fractures with mortality (p=0.06), Yadollahi et al in their work reported more than thrice the risk of mortality in blunt trauma patients with rib fractures. Their mortality risk was not associated with hemothorax (p≥0.05) [ 4 ] as in our study. Literature has reported varying frequencies of hemothorax, hemopneumothorax, pneumothorax, rib fractures, and lung contusions in patients with thoracic trauma [ 6 , 11 , 17 , 18 ].…”
Section: Discussionsupporting
confidence: 71%
“…Traumatic thoracic injuries are commonly blunt in nature and affect middle-aged men (30-60 years). Males are more prone as they are mobile and engaged in high-risk activities [ 4 ]. The majority of BCIs are a result of RTAs; other common causes include fall from height, assault, and occupational injuries [ 2 - 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations